Konsep Pendidikan Akhlak Dalam Perspektif Al-Qur’an Surat Luqman Ayat 12-19. - Solihin Solihin (LPPM STAI La Tansa Mashiro, 2015)
This research is the negative impact of globalization is a change that leads to a moral crisis, as well as a complex debate engulfing this beloved country due to morals, various currents of globalization with its developing technology associated with developments, good and negative information that can be easily accessed by rooms / House. Without the presence of strong provisions in religious cultivation (which have been included in moral values) it will have a negative impact if it is not properly filtered. Actually Islam has a good and ideal strategy concept. However, in practice, because Muslims themselves start neglecting and continue religious teachings, this concept becomes blunt and eroded in the face of the challenges of the times. On the contrary, they also do not fortify their future generations to avoid such values and culture. And everything must be returned to the Qur'an which becomes our guideline as Muslims. Based on this, it is necessary to apply the concept of moral education in an Islamic perspective.Based on the background of the above problems, this study chooses the purpose (1) To find the values of moral education contained in Surah Luqman verses 12-19 (2) To find out the application of moral education in accordance with daily life, the view of QS Luqman verse 12-19. This research is a type of qualitative research and is included in the literature study category (literature study), with descriptive-analytical research types. Data collection techniques used in this study are observation, interview, and literature studies. Furthermore, after the required data collected is then carried out using the deductive-inductive analysis method. This research is Luqman's letter verses 12-19 study of the interpretation of the tahlili. Library research methods (library research). The analysis used is content analysis and transferred using the tahlili method ... The analysis of moral values in the perspective of Luqman's letter verses 12-19 is: the meanings in these verses are some things that give messages of moral values. Among moral education to Allah SWT, moral values to both parents, and moral values to others.Based on the results of this study, it can be concluded that the values of moral education contained in the letter of Luqman paragraph 12-19 are (a) Educational gratitude, (b) Filial Education for parents, (d). Intellectual Education (e) Prayer Education (f )) Prohibited and self-help prohibitions. Coreresponding Author:Solihin124@gmail.com Coreresponding Author:Solihin124@gmail.com Coreresponding Author:Solihin124@gmail.com Penelitian ini adalah dampak negatif dari arus globalisasi yaitu perubahan yang mengarah pada krisis akhlak, sehingga menimbulkan sejumlah permasalahan kompleks melanda negeri tercinta ini akibat akhlak, beberapa permasalahan arus globalisasi dengan teknologinya yang berkembang pesat merupakan tantangan tersendiri dimana informasi baik positif maupun negatif dapat langsung diakses dalam kamar/rumah. Tanpa adanya bekal yang kuat dalam penanaman agama (yang telah tercakup di dalamnya nilai akhlak) hal itu akan berdampak negatif jika tidak di saring dengan benar. Sebenarnya Islam sendiri memiliki konsep strategi yang baik dan ideal. Akan tetapi dalam prakteknya, dikarenakan umat Islam sendiri yang mulai lalai dan meninggalkan ajaran agama, konsep tersebut menjadi tumpul dan seolah terkikis dalam menghadapi tantangan zaman. Bahkan mereka juga tidak membentengi para generasi penerusnya agar terhindar dari nilai dan budaya yang demikian. Dan semuanya harus di kembalikan kepada Al-Qur’an yang menjadi pedoman hidup kita sebagai umat Islam.Berdasarkan hal ini, maka diperlukan penerapan konsep pendidikan akhlak dalam perspektif Islam. Berdasar latar belakang masalah diatas maka penelitian ini memilih tujuan (1) Untuk mengetahui nilai-nilai pendidikan akhlak apa saja yang terkandung dalam surah Luqman ayat 12 – 19 (2) Untuk mengetahui penerapan pendidikan akhlak kedalam kehidupan sehari-hari perspektif Q.S Luqman ayat 12-19.Penelitian ini merupakan jenis penelitian kualitatif dan termasuk kategori studi kepustakaan (library research), dengan sifat penelitian deskriptis-analitis. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik observasi, wawancara, dan kajian pustaka. Selanjutnya, setelah data yang dibutuhkan terkumpul kemudian dianalisis dengan menggunakan metode analisis deduktif-induktif. Penenlitian ini adalah surat Luqman ayat 12-19 studi tafsir tahlili. Metode penelitian pustaka (library research). Analisis yang digunakan adalah analisis isi dan ditafsirkan dengan menggunakan metode tahlili.Analisis terhadap nilai-nilai pendididkan akhlak dalam perspektif surat Luqman ayat 12-19 adalah : bahwa dalam ayat-ayat tersebut terdapat beberapa hal yang memberikan pesan-pesan nilai akhlak. Diantaranya pendidikan akhlak terhadap Allah SWT, nilai-nilai akhlak terhadap kedua orang tua, dan nilai-nilai akhlak terhadap sesama. Berdasarkan hasil penelitian ini dapat disimpulkan nilai-nilai pendidikan akhlak yang terkandung dalam surat luqman ayat 12-19 adalah (a) Pendidikan syukur, (b) Pendidikan Berbakti kepada kedua orang tua, (d).Pendidikan Intelektual (e) Pendidikan Sholat (f) Larangan sombong dan membanggakan diri.